Gambaran Pengetahuan Akseptor KB Suntik 3 Bulan tentang Efek Samping KB Suntik 3 Bulan: Knowledge Description of 3 Months Injectable KB Acceptors about Side Effects of 3 Months Injectable KB - Arsesiana, Angga; Hertati, Dessy; Oktarina, Lelly; Utami, Dian Tri (Jurnal Surya Medika (JSM), 2022)
Background: One contraceptive method used to regulate the birth of a child is a 3-month injection of KB or Depo Medroxy Progesterone Acetate (DMPA). Controversy about the side effects of 3-month injectable contraceptives, such as menstrual cycle disorders, vaginal discharge, and weight gain, has become a problem in the community, so mothers are reluctant to use this contraceptive method. Mothers' ignorance about the side effects of 3 months causes fear of mothers using 3-month injectable contraception. Research objectives: To determine the level of knowledge of 3-month injectable family planning acceptors about the side effects of 3-month injection family planning. Methods: The research design used descriptive research using the literature study or literature review method. To search for literature using PICOS, the population inclusion criteria are 3-month Injectable Family Planning Acceptors, descriptive study design, articles published from 2018 to 2021, and articles in Indonesian. Results: From the results of the literature review in the first article, the majority of respondents' knowledge was in the poor category 21 (58.3%); in the second article, the majority of respondents who had good knowledge, 36 (54.5%) and the third article the majority of respondents who had less knowledge 36 (50,7%). Conclusion: Most of the respondents' knowledge level is lacking. This is because a person's knowledge can be influenced by age, education, occupation, and sources of information. To increase the knowledge of family planning acceptors in conveying information to the community, it is necessary to know the characteristics of the community. When conveying information, they can use assistive media easily understood by the community.